BIMBINGAN KELOMPOK DENGAN PENDEKATAN TIME MANAGEMENT SEBAGAI UPAYA PENINGKATAN SELF-REGULATED LEARNING MAHASISWA MANAJEMEN PENDIDIKAN ISLAM INSTITUT AGAMA ISLAM NGAWI TAHUN 2020/2021 - Nabella Dananier; Nurmalia Khotimah (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2021)
abstract Students basically have good knowledge and skills if they are able to organize themselves. Most of the second semester MPI students of IAI Ngawi are already working and living in Islamic boarding schools which have a lot of religious activities in them. So that students' academic self-regulation is not good because they have not been able to manage their time optimally. This shows the lack of student self-regulated learning. To overcome this, group guidance or group guidance using the Time Management approach is one form of effort used to assist students in improving their academic self-regulation. From the results of this study, it is known that group guidance with a time management approach is able to improve self-regulated learning for second semester MPI students. The implementation of group counseling with a time management approach begins with prioritizing important tasks, developing plans, continuously monitoring deviations, and finally reducing pressure on the schedule. Meanwhile, academic self-regulation begins with recognizing and discovering one's potential, ending with building a group to grow together. group counseling with a time management approach, students succeeded in improving their academic self-regulation as evidenced by data from interviews and documentation of increasing student discipline in collecting assignments. Keyword : Group Guidance, Self-Regulated Learning, Time Management